RESISTENSI BAKTERI ORAL BIOFILM TERHADAP ANTIBIOTIKA GOLONGAN BETA-LAKTAM - Yani Corvianindya; Sunarso Brotosoetarno (Faculty of Dentistry, Universitas Indonesia, 2015)
The multi species oral bacterial biofilm contributes to plaque formation, tooth caries, infection of oral mucosa and also periodontal disease. Caries prevention is possible by controlling the bacterial population, eg by application of antibiotics. The use of antibiotics in this way is not curative but still effective on topical application. Betalactam antibiotics are drugs of choice because most oral infections are caused by mixture of anaerobic bacteria. The peptidoglican reaction in bacterial cell walls by betalactam results in bacterial lysis. Recently, bacterial resistance to betalactam antibiotics has been found to occur frequently by several cellular mechanisms, such as bacterial production of β-lactamase, mutation of penicillin-binding protein (PBP) with low affinity to antibiotics, or decrease of cell wall permeability to betalactam. Bacteria can acquire resistance genes by mutation or exchange of genes.